Out of the study and into the field : ethnographic theory and practice in French anthropology. - Parkin, Robert; Sales, Anne de (Methodology and history in anthropology ;, 2010)
Outside France, French anthropology is conventionally seen as being dominated by grand theory produced by writers who have done little or no fieldwork themselves, and who may not even count as anthropologists in terms of the institutional structures of French academia. This applies to figures from Durkheim to Derrida, Mauss to Foucault, though there are partial exceptions, such as Lévi-Strauss and Bourdieu. It has led to a contrast being made, especially perhaps in the Anglo-Saxon world, between French theory relying on rational inference, and British empiricism based on induction and generally skeptical of theory. While there are contrasts between the two traditions, this is essentially a false view. It is this aspect of French anthropology that this collection addresses, in the belief that the neglect of many of these figures outside France is seriously distorting our view of the French tradition of anthropology overall. At the same time, the collection will provide a positive view of the French tradition of ethnography, stressing its combination of technical competence and the sympathies of its practitioners for its various ethnographic subjects -- Présentation de l'éditeur.